Cultivo de saccharomyces cerevisiae em processos descontínuo e descontínuo alimentado utilizando mel invertido para produção de etanol - Silva, Fernando Henrique da (2016)
In this work were performed fermentative tests using as substrate honey of sugar and alcohol plant and using the micro-organism in the form of fresh pressed yeast, at the temperature of 32°C and with cells concentration on dry basis of 15 g/L, and having as variables the previous inversion or non-inversion of the saccharose of the honey, the initial concentrations of Total Reduced Sugars (TRS) (150, 200 and 250 g/L) and the way of operation of the fermentations (batch, fed-batch in pulses and fed-batch with constant alimentation). In these experiments, samples of must were collected every half an hour or every hour, and the concentrations of TRS (Substrate) (S), Ethanol (Product) (P) and Cells (X) of the samples were analyzed. It was used for the concentration analysis: of TRS, the Modified 3,5 - Dinitrosalicilic Acid (DNS) method; of Ethanol, microdestilation followed by gas chromatography analysis; and Cells, adequate dilutions of the yeast existing in the must and reading in spectrophotometer. With this, it was possible to analyze the rates of consumption of TRS, production of ethanol and cells growth, as well as the factors of conversion of the substrate in product (YP/S) and in cells (YX/S). It was observed higher values of (YP/S) in the fermentations with previous inversion of the saccharose (0,429 g Ethanol/ g TRS) when compared with the fermentations that not suffered this process (0,382 g Ethanol/ g TRS). However, at high concentrations of TRS ( 200 and 250 g/L), in the batch fermentations, it was observed lower values of reaction rates to the fermentations with previous inversion (27,0 g TRS/ L.h e 10,1 g Ethanol/ L.h) when compared to the without inversion (14,6 g TRS/ L.h e 6,1 g Ethanol/ L.h). It was obtained higher values of (YP/S) in the fed-batch fermentations (0,413 g Ethanol/ g TRS) when compared with the batch (0,396 g Ethanol/ g TRS). It was observed higher reaction rates to the batch fermentations (28,3 g TRS/ L.h e 10,5 g Ethanol/ L.h) comparatively to the fed-batch fermentations (21,2 g ART/ L.h e 8,4 g Ethanol/ L.h) for the fermentations without previous inversion of the saccharose, and it wasn't observed great effects in the reaction rates due to the way of operation adopted in the fermentations with previous inversion of the saccharose.